Leptin Induces Cyclin D1 Expression and Proliferation of Human Nucleus Pulposus Cells via JAK/STAT, PI3K/Akt and MEK/ERK Pathways - Li, Zheng; Shen, Jianxiong; Wu, William Ka Kei; Yu, Xin; Liang, Jinqian; Qiu, Guixing; Liu, Jiaming (PloS one, 2012)
Increasing evidence suggests that obesity and aberrant proliferation of nucleus pulposus (NP) cells are associated with intervertebral disc degeneration. Leptin, a hormone with increased circulating level in obesity, has been shown to stimulate cell proliferation in a tissue-dependent manner. Nevertheless, the effect of leptin on the proliferation of human NP cells has not yet been demonstrated. Here, we show that leptin induced the proliferation of primary cultured human NP cells, which expressed the leptin receptors OBRa and OBRb. Induction of NP cell proliferation was confirmed by CCK8 assay and immunocytochemistry and Real-time PCR for PCNA and Ki-67. Mechanistically, leptin induced the phosphorylation of STAT3, Akt and ERK1/2 accompanied by the upregulation of cyclin D1. Pharmacological inhibition of JAK/STAT3, PI3K/Akt or MEK/ERK signaling by AG490, Wortmannin or U0126, respectively, reduced leptin-induced cyclin D1 expression and NP cell proliferation. These experiments also revealed an intricate crosstalk among these signaling pathways in mediating the action of leptin. Taken together, we show that leptin induces human NP cell cyclin D1 expression and proliferation via activation of JAK/STAT3, PI3K/Akt or MEK/ERK signaling. Our findings may provide a novel molecular mechanism that explains the association between obesity and intervertebral disc degeneration.